On Micromechanical Modeling of Deformation of Compact Rock in Compression - Basista, M. (Engineering Transactions, 1993)
The paper proposes a simple two-dimensional damage model for low-porosity rocks loaded in compression. The sliding crack mechanism is selected as an underlying micromechanism of the inelastic deformation at the macroscale. A numerical example is worked out showing the capability of the model for duplicating the experimentally observed trends of rock deformation.